Mathematics Teachers’ Reflection on Essential Digital Skills and Techniques for Effective Online Mathematics Instruction - Khanal, Bishnu; Joshi, Dirgha Raj; Sharma Chapai, Krishna Prasad (Education and Development, 2022)
Digital skills are necessary to integrate novel technologies in instructional practices of each subject including mathematics. The aim of this research was to explore the necessary skills for teaching mathematics and practical ways to teach mathematics online. The qualitative survey design was used among 277 mathematics teachers in Nepal through open questionnaires using Google Form. The list-based sampling strategy was used to collect the data. The results were analyzed by using word cloud and descriptive methods. The findings indicate that every mathematics teacher should have skills in using different tools like video conferencing, collaboration, subject-specific software, visualization, and LMS. Furthermore, an access to the internet, digital devices, and resources is necessary for all teachers and students in this age. Skill development, use of novel instructional activities, use of digital tools, resource management, and development, collaboration, and communication are the key areas of mathematics teachers for effective teaching online.